Medical discipline and licensing in the State of New York: a critical review. - Post, J. (1991)
This review examines the current medical disciplinary process in New York State and assesses whether it protects the public and is fair to respondent physicians. Clearly there is urgent need for reform. Results of 1,036 disciplinary actions over the years 1982-1989 have been reviewed, with special attention to the 878 cases during 1985-89. The types of misconduct and their incidences among these physicians represent but a small segment of the more than 40,000 licensed practising physicians in this state. Extrapolations concerning their incidence should not be made from these limited data to the general population of physicians. The many flaws in the present system have been noted. A brief review of the process in 32 other states, Ontario, and Great Britain has shown that New York's is the most cumbersome and lengthy. Changes are suggested to modify the present system preserving some features of the current process but eliminating others. Licensing and disciplinary processes should be included in a single agency within the Health Department and this must be kept independent.